Study on Time-related Changes in Aerobic Bacterial Pattern of Burn Wound Infection - Saha, SK; Muazzam, N; Begum, SA; Chowdhury, A; Islam, MS; Parveen, R (Faridpur Medical College Journal, 2011)
A prospective study was carried out in 50 burn patients admitted in Burn unit of Dhaka Medical College Hospital over a period of one year from January 2005 to December 2005 to evaluate time-related changes in aerobic bacterial colonization and their sensitivity pattern. Periodic swabs were taken from the burn wound on Day 0, Day 7, Day 14 and Day 21 to see the changing pattern of organisms during hospital stay of patients. In the present study burn injury was highest in the age group 11-20 yrs (34%). Male to female ratio was 1.38:1. The mean percentage of burn was 35.79% of total body surface area (TBSA). Fire was the major cause of burn (38%) followed by electric burn (20%). Among the 200 samples, single organism was isolated in 71% samples and mixed organism in 13.5% and no growth in 14.5%. Among single isolates Pseudomonas aeruginosa was leading (28%) followed by Escherichia coli (17.5%), Staphylococcus aureus (16%), coagulse negative Staphylococcus (4.5%) and Klebsiella (2%). Among mixed growth Pseudomonas aeruginosa was still leading (11%) follow by E. coli (9.5%) Staphylococcus (5.5%), Proteus (1%) and Klebsiella (0.5%).There were time -related changes in bacterial isolation from burn wound during hospital stay of patients. On admission 42% of the isolated organisms were Staphylococcus aureus and only 6% each Pseudomonas aerunginosa and E. coli were isolated. No growth was found in 28%. samples. These findings were gradually changing with time and on day 21 Staphylococcus aureus were only 4% whereas Pseudomonas aeruginosa were 40% and E. coli 28%. Antimicrobial sensitivity test showed that pseudomonas aeruginosa was highly resistant to antimicrobial agents. It was most sensitive to Imipenem (98.72%) followed by Aztreonam (33.44%), Ceftazidime (38.32%) and Gentamicin (19.23%). E. coli was also found most sensitive to Imipenem (98.15%) followed by Gentamicin (38.95%), Chloramphenicol (37.1%), Ciprofloxacin (35.25%) and ceftraixone (29.70%). Staphylococcus aureus was 100% sensitive to Vancomycin followed by Amoxiclav and Oxacillin (53.43% each), Gentamicin (44.70%) and Cloxacillin (39.52%). It is crucial for every burn institution to determine the specific pattern of burn wound microbial colonization, the time-related changes in dominant flora, and the antimicrobial sensitivity profiles. This would enable early treatment of septic episodes with proper empirical systemic antibiotics without waiting for culture results, thus improving overall infection related morbidity and mortality. DOI: 10.3329/fmcj.v6i1.7410 Faridpur Med. Coll. J. 2011;6(1): 41-45